Energy reform in Switzerland: A quantification of carbon taxation and nuclear energy substitution effects - Peter Egger; Sergey Nigai (ETH Zurich, KOF Swiss Economic Institute, 2013)
We develop a general equilibrium model of trade with multiple countries and industries in the spirit of Eaton and Kortum (2002) and Bernard, Eaton, Jensen, and Kortum (2003). We structurally estimate the parameters of the model and calibrate it to data on 33 OECD countries and one country that covers the rest of the world. Industries differ by their relative energy intensity and the level of pollution. Accordingly, the implementation of policy instruments to reduce pollution at the country level induces heterogeneous effects across industries within and across countries. We utilize the model to compare alternative environmental tax instruments and to evaluate their consequences for the level of carbon emissions, welfare costs, industry-specific prices and demand in various policy scenarios. Among the latter, we particularly distinguish between policies that are implemented in isolation (by single countries) or en bloc (in groups of countries or even world wide). This study pays specific attention to the implementation of various energy policies, in particular, in Switzerland. Beyond implementation of the Copenhagen Accord pledges, the study quantifies an implementation of extra taxes on carbon emissions at the amount of 1,140 Swiss Francs per ton of carbon and the substitution of nuclear energy production.
Keywords: F11; F14; Q43; Q48; 330; Carbon taxation; Energy policy; International trade; Ökosteuer; Energiepolitik; Makroökonomischer Einfluss; Produktivität; Allgemeines Gleichgewicht; Außenhandelssektor; Außenwirtschaftstheorie; Schweiz